AN EMPIRICAL STUDY OF MOTIVATION OF POST GRADUATE STUDENTS TOWARDS STUDIES IN RELATION TO ECONOMIC CONDITION UNDER GAUHATI UNIVERSITY OF ASSAM (International Journal of Food and Nutritional Sciences, 2022)
The present study is focused on the Motivation of post-graduate students towards studies in relation to economic condition under Gauhati University of Assam. The present study aims at finding out whether there are significant differences between the motivation and adjustment among university students of Assam. The present investigation is descriptive survey method used. For this purpose, a sample of 80 students was randomly selected from Gauhati University. The present investigator has observed into light some investigating result that indicates the Male and Female batter result towards Arts Streams and Science Streams, which is intellectual dimension significant only, but the result of other factor of motivational between the male and female post-graduate students of Gauhati University differ statically significant at both levels. It is critical observation there are significant difference between factor of physical, social, moral educational and temperamental status character towards motivation.